2014
DOI: 10.1155/2014/493825
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Transcriptome Study to Develop Molecular Resources of the CopepodCalanus sinicusfor Their Potential Ecological Applications

Abstract: Calanus sinicus Brodsky (Copepoda, Crustacea) is a dominant zooplanktonic species widely distributed in the margin seas of the Northwest Pacific Ocean. In this study, we utilized an RNA-Seq-based approach to develop molecular resources for C. sinicus. Adult samples were sequenced using the Illumina HiSeq 2000 platform. The sequencing data generated 69,751 contigs from 58.9 million filtered reads. The assembled contigs had an average length of 928.8 bp. Gene annotation allowed the identification of 43,417 unige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…PRJNA234316 ). Yang et al [ 58 ] reported 31 GST proteins in the de novo transcriptome of the calanoid Calanus sinicus , but to date, these data are not publicly accessible. None of these studies included annotations by GST class or subclass, or protein structural analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRJNA234316 ). Yang et al [ 58 ] reported 31 GST proteins in the de novo transcriptome of the calanoid Calanus sinicus , but to date, these data are not publicly accessible. None of these studies included annotations by GST class or subclass, or protein structural analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, in general, it appears that the number of GST genes in these copepod species exceeds 30 based on automated annotations of TSA data (e.g. [ 58 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, adapter sequences were removed using SeqPrep v1.33. Moreover, sequences <100 bp and those with quality <20 as well as reads containing an N base were removed using Sickle v1.2; then, clean reads were created (Yang, Sun, Yang, & Li, ). Nonbacteria sequences (algae, protist, etc) were also cleaned by local Blastn program against NR database (V20151204) from NCBI with evalue 1e‐10 (Camacho et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The red labels are the sampling sites that located at the north bank of the estuary, the A, B, C, and D are mangrove sampling sites, and the E is a sandy beach site outside the mangrove. The yellow labels are the south bank sites, all of them are sandy beach sites Z <20 as well as reads containing an N base were removed using Sickle v1.2; then, clean reads were created (Yang, Sun, Yang, & Li, 2014).…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…The total RNA concentration and integrity were determined using an Agilent 2100 Bioanalyzer and a NanoDrop spectrophotometer (Thermo Scientific), respectively. RNA-seq library construction and sequencing (Illumina) were performed as described by Yang et al (2014). After the mRNA was enriched by beads with Oligo(dT) primers, the mRNA was dissected into short fragments.…”
Section: Rna Extraction and Sequencingmentioning
confidence: 99%